2019
DOI: 10.1002/cssc.201901384
|View full text |Cite|
|
Sign up to set email alerts
|

Fabrication of Trifunctional Polyoxometalate‐Decorated Chitosan Nanofibers for Selective Production of 2,5‐Diformylfuran

Abstract: Figure 7. Reusability and leaching amountofH PMoV/CS-f(25)int he oxidationo fH MF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
0
12
1
Order By: Relevance
“…[36,[51][52][53][54][55] Therefore, catalysts containing vanadium and molybdenum could be considered as main candidates for targeting the conversion of 5-HMF to DFF. Our [10,[47][48][49] Our results showed that the conversion and selectivity of converting 5-HMF to DFF depended on the amount of H 5 PMo 10 V 2 O 40 , the basic sites of support, and the Brønsted acidic sites of the hybrids. Compared to neutral or acidic supports, basic supports might provide weak basic sites favoring for oxidation of -OH group in 5-HMF.…”
Section: Introductionmentioning
confidence: 71%
“…[36,[51][52][53][54][55] Therefore, catalysts containing vanadium and molybdenum could be considered as main candidates for targeting the conversion of 5-HMF to DFF. Our [10,[47][48][49] Our results showed that the conversion and selectivity of converting 5-HMF to DFF depended on the amount of H 5 PMo 10 V 2 O 40 , the basic sites of support, and the Brønsted acidic sites of the hybrids. Compared to neutral or acidic supports, basic supports might provide weak basic sites favoring for oxidation of -OH group in 5-HMF.…”
Section: Introductionmentioning
confidence: 71%
“…Among various biomass‐derived products, 5‐hydroxymethylfurfural (HMF), generated from acid‐promoted dehydration of C6 carbohydrates, has been widely identified as a versatile platform chemical with high industrial potentials [8] . Under appropriate conditions, HMF could undergo oxidation to different furanic products: 2,5‐furandicarboxylic acid (FDCA), [9] 2,5‐diformylfuran (DFF), [10] 5‐hydroxymethyl‐2‐furancarboxylic acid (HMFCA), [11] and 5‐formyl‐2‐furancarboxylic acid (FFCA), [12] which all bear modifiable functional groups of hydroxyl group, carboxylic acid group and an aldehyde group, as well as a furan ring for further versatile applications (Scheme 1). For example, FDCA, as one of the top‐12 value‐added chemicals from biomass resources by the U.S. Department of Energy, is the key monomer of functional bio‐polymers, [13] HMFCA and FFCA work as not only an important raw material for the synthesis of tetramer macrocyclic oligoester native ionophore antibiotic, [14] but also a valuable structural unit of an interleukin inhibitor [15] or other high‐value chemicals, [16] while DFF has very promising potential applications in synthesizing functional polymers, [17] fungicides, [18] pharmaceuticals, [19] heterocyclic ligands [20] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent few years, the use of polyoxometalate (POMs) as homogeneous or supported heterogeneous catalysts to convert HMF into other value-added products has attracted wide attention due to their attractive features like tunable acidity and redox property, oxidative and thermal stability, strong UV light-absorbing ability, and highly adjustable structures. [21] For instance, plenary or transition-metal-substituted Keggin type POMs have been widely studied in oxidizing HMF to various products such as maleic acid and maleic anhydride, [22] DFF, [10,23] FDCA. [24] In addition, taking advantage of strong Brønsted acidity, they also show extraordinary talents in cellulose hydrolysis, [25] fructose to HMF conversion and directly synthesis of DFF from carbohydrates, [26] etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,5‐Diformylfuran (DFF) is a versatile compound that has various applications, including as a polymeric monomer and a promising cross‐linking agent for battery separation, in pharmaceuticals, antifungal agents, furan–urea resins, heterocyclic ligands and other value added products, which is synthesized predominantly via the oxidation of 5‐hydroxymethylfurfural (HMF). However, this transformation can be accompanied by the formation of several other kinds of furan compounds like 2,5‐furandicarboxylic acid, 5‐formyl‐2‐furancarboxylic acid and 5‐hydroxymethyl‐2‐furancarboxylic acid . Thus, for DFF production, highly selective oxidation of HMF is important.…”
Section: Introductionmentioning
confidence: 99%